Import control and industrialization: a study of the Australian experience - Moffatt, Graeme Gilbert ([Melbourne] Melbourne University Press, 1970)
This study of the Australian experience of industrialization under the shelter of import controls and tariffs covers the eight years of import licensing from 1952 until 1960 and the subsequent seven years, which saw the imposition of highly controversial tariffs to replace the protective effect of the controls.
Based on dissertation, Melbourne University.
Bibliography: p. 181-183.
occ 17/01/2019
Loans
Keywords: Import quotas; Tariff; Australia